‘Amaliyyah al-Andragogiya li Mu’allim al-Lughah al_juhûd li Tarqiyyah al-Kafâ’ah al-Tarbawiyyah - Faliqul Isbah; M. Fairuz Rosyid (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2021)
Abstract: Teachers have an obligation to provide quality teaching. Therefore, teachers always try to develop pedagogical competencies. One of the paths taken by the teacher to achieve that goal is by practicing a lifelong learning culture or andragogy. Starting from this problem, this study aims to examine the learning culture of Arabic teachers in improving pedagogical competence. The principles and characteristics of andragogy theory are used to develop research. The study uses qualitative methods with interview data collection techniques. While the research subjects were Arabic language teachers at the High School level and equivalent in Pekalongan. Data analyzed with Miles and Hubermen stages include, data collection, data reduction, data presentation and drawing conclusions. The practice of andragogy of Arabic teachers in Pekalogan can be said to be good and centered on developing pedagogical and professional competencies while social and moral competencies are the driving force of teachers to do lifelong learning. Keywords: andragogy, Arabic language teacher and pedagogical competence. Abstrak: Guru memiliki kewajiban untuk memberikan pengajaran yang berkualitas. Oleh karena itu, guru senantiasa berusaha untuk mengembangkan kompetensi pedagogik. Salah satu jalan yang ditempuh oleh guru untuk mencapai tujuan itu ialah dengan mempraktikkan budaya belajar sepanjang hayat atau andragogi. Bertolak dari permasalahan tersebut, penelitian ini bertujuan untuk mengkaji budaya belajar guru bahasa Arab dalam meningkatkan kompetensi pedagogik. Prinsip dan ciri teori andragogi digunakan untuk mengembangkan penelitian. Penelitian menggunaan metode kualitatif dengan teknik pengumpulan data wawancara. Sementara subyek penelitian adalah guru bahasa Arab tingkat Sekolah Menengah Atas dan sederajat di Pekalongan. Data dianalasis dengan tahapan Miles dan Hubermen meliputi, pengumpulan data, reduksi data, penyajian data dan penarikan simpulan. Praktik andragogi guru bahasa Arab di Pekalogan dapat dikatakan baik dan berpusat pada pengembangan kompetensi pedagogik dan kompetensi profesional sementara kompetensi sosial dan moral merupakan daya dorong guru untuk melakukan belajar sepanjang hayat. Kata kunci: andragogi, guru bahasa Arab dan kompetensi pedagogik.